Fostering the future: Agripreneurship intentions among Indian agricultural students - Amaran K; Anbu Krishnamoorthy; Palanisamy Shobana (Heliyon)
India is an agrarian country, but the contribution of agriculture to GDP was reduced gradually. It was due to the decline of land resources, climate change, and low profitability. To overcome these problems, agripreneurship can offer a viable solution and foster innovation and economic viability which is easily adopted by the younger generation. So, this study focuses on the agricultural college students who have more scope to start an agribusiness. It explores attitudes, subjective norms, perceived behavioural control, agripreneurship education, personality traits, and their relationship with agripreneurship intention among 210 agriculture students in India, the study employed a descriptive research design, with data collected through an online survey. Purposive and snowball sampling techniques were utilized to reach the target population. Data analysis was conducted using SPSS, employing t-test, ANOVA, correlation, and multiple linear regression to examine the relationships and differences among variables. and the theory of planned behaviour was used to explain the complex relationship between the variables. The results showed that attitudes, subjective norms, perceived behavioural control, and personality traits substantially predict agripreneurship intention, and formal agripreneurship education appears to have minimal influence on outcomes. Gender, landholding, major family occupation, nativity, course of study, and family background do not substantially impact agribusiness plans. The study offers insights for educational institutions, governments, and other stakeholders interested in promoting agripreneurship and driving innovation in agriculture in India. These findings emphasise the need for a comprehensive strategy to foster agribusiness goals that cross traditional boundaries and contexts.